(untitled) - Johnson, Randy (New York, 2002)
Finding the right mortgage can be complex, confusing, and frustrating. But that doesn't mean you have to settle for anything other than the terms you want. This indispensable and newly updated second edition of How to Save Thousands of Dollars on Your Home Mortgage spells out everything mortgage hunters need to know in clear and accessible terms. It covers more loan alternatives than any other book and examines the importance of discount points. It offers complete details on virtually every mortgage option currently available, what advantages each option offers, how to choose the right one for your needs, and how to save money in the process. New information in this edition will help you use the Internet to find a home and get a mortgage, examine automated underwriting models and conforming loan limits, and weigh new shopping strategies.
Keywords: Mortgage loans,Cho vay thế chấp; United States,Hoa Kỳ